Kepadatan Jentik Nyamuk Aedes sp. (House Index) sebagai Indikator Surveilans Vektor Demam Berdarah Dengue di Kota Semarang - Ummi Khairunnisa; Nur Endah Wahyuningsih; Hapsari Hapsari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Dengue Hemorrhagic Fever (DHF) is one of major health problem in Indonesia. DHF is a caused by the dengue virus and transmitted by Aedes aegypti.The number of mosquito breeding places and larvae density become risk factor influenced the spreading of mosquitoes. House index (HI) was an indicator to know the houses that have larvae. The purpose of this study was to describe House Index (HI) in Semarang City and surrounding areas. This study was descriptive with cross sectional study. The population of this study are all of houses in Semarang City and surrounding areas. The sample had taken by purposive sampling methode. Data was colleted through interviews and field observation to 54 respondents. Larvae survey with visual method to count the larvae indices (HI). Dengue transmission risk was categorized mild, moderate and severe base on density figure. The result of study showed that HI (44,44%) and DF (6) in Semarang City. Based on HI, have a high risk of transmission to the spread of dengue disease.